Tinnitus-associated cognitive and psychological impairments: a comprehensive review meta-analysis - Yang, Dong; Zhang, Dan; Zhang, Xinmiao; Li, Xin (Frontiers in Neuroscience, 2024)
Background Tinnitus is strongly associated with an increased risk of cognitive disabilities. The findings of this research will provide valuable support for future investigations aimed at determining the correlation between tinnitus and the risk of cognitive impairments. Objectives We investigated the potential correlation between tinnitus and the risk of various cognitive impairments, such as dementia, compromised learning attention, anxiety, depression, and insomnia. The study examined this relationship collectively and by categorizing the data based on different age groups. Methods We compiled data from case–control studies and cohort studies obtained from reputable databases such as PubMed, Cochrane Library, and Embase. To minimize potential bias, two reviewers independently assessed the selected articles. After extracting the data, we calculated the pooled odds ratios (ORs) using a random-effects model. Results Seventeen relevant studies, comprising an adult population, were included in this analysis. Pooled estimated outcomes revealed a strong association between tinnitus and an elevated risk of dementia-compromised learning, auditory attention, anxiety, depression, and poor sleep quality (P<0.05). Furthermore, the pooled analysis stratified by age demonstrated that patients aged above 60 years, in comparison to those aged 18 to 60 years, exhibited more significant outcomes in relation to the progression of cognitive impairments. Conclusion Tinnitus has the potential to increase the risk of cognitive impairments. Moreover, geriatric patients aged above 60 shows a higher susceptibility to developing cognitive disabilities compared to their younger counterparts.